Pigmented microcystic chromophobe cell carcinoma: a unique variant of renal cell carcinoma - Michal, M; Hes, O; Svec, A; Ludvíková, M (Annals of diagnostic pathology, 1998)
Five cases of pigmented chromophobe renal cell carcinoma are presented. The patients included four men and one woman between the ages of 60 and 73 years (median age, 66.5 years), who presented with symptoms due to their renal mass. Surgical resection of the renal mass was performed in all patients. Grossly, the tumors were well encapsulated, yellow to dark gray, with a vague nodular pattern on cut surface. The tumors varied between 2.5 and 9 cm in greatest diameter. Histologically, all tumors shared similar features, namely, a malignant cellular proliferation composed of deeply eosinophilic to clear cytoplasm with round nuclei and inconspicuous nucleoli. The cellular proliferation was arranged in a microcystic and/or microalveolar pattern. In one tumor, conventional areas of clear cell carcinoma in association with the chromophobe component were present. In addition, all tumors contained pigmented areas, which were shown by light microscopy to have features of lipochrome pigment. Ultrastructural studies of these areas demonstrated the presence of intracytoplasmic polygonal to round, electron-dense pigment granules, which in some areas seemed to coalesce to form larger granules. In addition, numerous mitochondria and cytoplasmic vesicles were present. The cases described herein highlight an additional morphologic variant of chromophobe renal cell carcinoma.
Keywords: senioři; Carcinoma, Renal Cell; mitochondrie; lidé; Middle Aged; mužské pohlaví; pigmentace; karcinom z renálních buněk; Kidney Neoplasms; ženské pohlaví; cytoplazma; Humans; lidé středního věku; Mitochondria; Pigmentation; Cytoplasm; Female; Aged; nádory ledvin; Male